Efeito do estresse hídrico e salino na ger minação e vigor de se mentes de maxixe - Alves, Charline Zaratin [UNESP]; Santos Lourenço, Flávia Mendes Dos; Da Silva, Josué Bispo [UNESP]; Da Silva, Tiago Roque Benetoli [UNESP] (My University, 2014)
The objective of this work was to evaluate the germination and vigor of two lots of gherkin seeds in different osmotic potentials using polyethylene glycol (PEG 6000) and sodium chloride (NaCl). Seeds of the 'North' cultivar were sown in germitest paper moistened in solutions of polyethylene glycol and sodium chloride in osmotic potentials of 0, -0.3, -0.6, and -0.9MPa. The experimental design was completely randomized in a factorial 2×4 design (solutions × osmotic potential), with four replications. Seed vigor was evaluated by the germination test, first germination count, length and dry weight of root and hypocotyl. It is concluded that the reduction in osmotic potential from -0.3MPa induced by PEG 6000 and NaCl reduces the germination and vigor of gherkin's seeds. The osmotic stress induced by PEG 6000 produced more severe effects than saline in physiological quality of gherkin's seeds.
Effect of water and saline stress on germination and vigor of gherkin seeds